Toward a better understanding of implementation performance in the EU multilevel system - Thomann, Eva; Sager, Fritz (Journal of European public policy, 2017)
The results of this collection allow for preliminary conclusions about the nuanced interplay between Europeanization and domestication forces in European Union (EU) implementation, which await testing in different contexts. Some policies lend themselves more to a strategy allowing for extensive domestication than others; but to be effective, decentralized implementing actors need both power and capabilities. Europeanization dynamics strongly influence the direction of domestication of EU policy, but if EU requirements are incompatible with national political preferences domestication trumps Europeanization. Domestication equally prevails if the relationship between EU and national policy is ambiguous and frontline implementers have high discretion. The trend toward the Europeanization of direct EU enforcement challenges its legitimacy. This has implications for EU researchers and practitioners, and suggests methodological challenges and future research trajectories for a performance perspective on EU implementation. More comparative research is needed about the trade-offs between conformance, diversity, and performance in EU multilevel governance.
Gesehen am 26.04.2018